Dampak Berganda Pada Objek Wisata Pantai Meleura - Muhamad Isa Ramadhan; Irfan Rifani (Jurnal Penelitian Pendidikan Geografi, 2022)
Meleura Beach is one of the tourist attractions in Muna Regency. This tourist attraction was developed by the government and experienced an increase in visits after that. The presence of tourist objects and the increase in tourist visits also have an impact on the surrounding community, especially for the local economy. The research approach used is descriptive quantitative by using multiplier effect analysis to determine the impact of tourism activities on local communities. The results showed a multiple impact ratio index of 1.3, which means that tourism activities affect the income of the surrounding community in the sector of owners, managers and providers of tourism services. The impact of tourism is known in the form of direct impacts, which are obtained from tourist expenditures and indirect impacts, namely changes in the form of community economic activities from agricultural and fishery activities to the form of providing tourism services.